Acute Basilar Artery Occlusion: Treatment Challenges in a Complex Case with Concurrent Shingles and Post-COVID-19 - Logadarshini Rajagopal; Hazwani Ismail; Azliza Ibrahim (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Introduction: Acute basilar artery occlusion is a neurological emergency and can lead to considerable neurological deficits up to complete tetraplegia, comatose states, and finally lethal outcomes if untreated. A decreased level of consciousness is most important in indicating BAO, requiring emergent treatment to restore blood flow and avert infarction. Therapy usually combines thrombolytics with mechanical thrombectomy for clearance of the occlusion. Case Report: A 71-year-old gentleman, known to have had hypertension, woke up with an unsteady gait. His baseline brain scan had shown an infarct in the left cerebellum. He had been on DAPT. By the next day, his symptoms were progressing, including difficulty walking and slurred speech. Further investigations showed multiple acute infarcts in the midbrain, pons, and cerebellum. Treatment was complicated because he had recently recovered from COVID-19 and shingles. The patient underwent angioplasty; DAPT was continued. Although he started showing improvement, there were some remaining neurological deficits that required ongoing rehabilitation. Conclusion: Coordinating the management of BAO in a patient with a complex medical history may require the input of multiple specialists. Ballooning as well as medical therapy are important in treatment, but decisions should be guided by the specifics of each case.